Classcraft Gamified Problem-Based Learning: How Does It Enhance Collaboration and Critical Thinking Skills? - Nurohman*, Sabar; Prakasita, Anindya Rizky; Rahmawati, Laifa; Maryanto, Allesius; Tyas, Rizki Arumning; Borhan, Mohamad Termizi bin (Universitas Syiah Kuala, 2025)
Conventional science education often fails to develop essential critical thinking and collaboration skills among students. This study investigates the impact of problem-based learning (PBL) augmented by classcraft gamification on enhancing these competencies. Utilizing an experimental design with a nonequivalent control group, data were gathered through pretests, posttests, and collaboration questionnaires. Analysis involved independent sample t-tests, Manova, and effect size calculations. The independent sample t-test demonstrated a significant difference between the experimental and control groups (p = 0.000 0.05), highlighting the intervention's effectiveness. Additionally, MANOVA results confirmed that the PBL model using classcraft significantly influenced both critical thinking and collaboration skills. With effect sizes of 1.78 and 1.48, the intervention was categorized as having a very high impact. These findings indicate that incorporating classcraft gamification into PBL not only enhances students' critical thinking and collaboration but also promotes a more engaging learning atmosphere. The implications of this study suggest a transformative approach to science education, encouraging educators to embrace innovative methods that cultivate vital 21st-century skills in students. By leveraging gamified learning experiences, educators can better prepare students for the complexities of modern problem-solving and teamwork